Finite Element Simulation on Soil Compaction Effect and Mechanical Properties of Precast Nodular Pile - Yongfa Wang; Baojian Li; Guoer Lv; Jiajin Zhou; Xianlin Jia (Geofluids)
The bearing capacity of traditional prestressed high-strength concrete (PHC) pipe pile is hampered by the poor mechanical properties of surrounding soil in soft soil areas, and the PHC nodular pile can improve the behavior of pile foundation in soft soils. The PHC nodular pile installation process will induce larger disturbance to the surrounding soil compared to the PHC pipe pile, and there is little research on the installation effect of the PHC nodular pile. In this paper, the coupled Eulerian-Lagrangian (CEL) finite element method was adopted to simulate the penetration process of PHC nodular piles and pipe piles in soft soil. The radial stress and displacement in soil induced by the PHC nodular pile and pipe pile and the soil resistance at different parts of the PHC nodular pile were analyzed. The simulation results showed that the penetration resistance of the PHC nodular pile was larger than that of the PHC pipe pile. The penetration resistance of PHC nodular piles was mainly provided by the pile shaft resistance. The uplift height of soil surface caused by the PHC nodular pile and pipe pile penetration was approximately the same. The influence range of compaction effect for PHC nodular pile and pipe pile was both concentrated on 10R (R is the pile diameter).